Pengaruh Kesehatan Lingkungan Terhadap Kejadian Diare dan Status Gizi Anak Umur 6 Bulan Sampai 59 Bulan di Kota Pekanbaru Provinsi Riau - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT Public health problems in the city of Pekanbaru, as any other city in Indonesia, are ranged in environmental health. Socio-economical factors like education, job, revenue level, and the amount of family members are affecting environmental health. Environmental health level can be measured by the amount of the diarrhoea incidents. Longer and more often diarrhoea suffered by children can cause declinations in nutritional status. The aim of this study was to know the factors that affecting the environmental health level, to know the effects of environmental health level to the diarrhoea incidents, and nutritional status of children between 6 to 59 months. This observational research was using Cohort prospective design. The research was taken place in the city of Pekanbaru. Samples were households, and the subjects were children between 6 to 59 months. Samples were collected using purposive random sampling with the amounts of the samples were 90 children. The exposed and non-exposed subjects to environmental health were observed for 3 months to diarrhoea incidents and the change of nutritional status using WHZ. Data was analysed using Chi square, logistic regression and double linear regression with level of significance p